Inokulasi Fungi Mikoriza Arbuskula (FMA) dan Pemupukan P untuk Meningkatkan Hasil dan Mutu Benih Cabai (Capsicum annuum L.) - Widi Agustin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
The research was carried out to investigate the effect of arbuscular mycorrhizal fungi (AMF) and phosphorus fertilizer on yield and seed quality of two genotypes of hot chilli pepper. The experiment was arranged in split-split plot with randomized block design, each with 3 replicates. The main plot was two pepper genotipes of Laris and Tegar, the sub plot was two AMF i.e without AMF and inoculation Mycofer AMF, the sub-sub plot was four dosages of phosphorus fertilizer, they are 0, 100, 125, and 150 kg P2O5 ha-1. Results showed that (1) genotype and AMF signifi cantly affected plant height; (2) genotypes interacted with AMF in affecting fruit and seed production; (3) interaction among genotip, AMF and phosporus fertilizer affected N, P, K content of seed, and N, P, K absorption of seed. For Laris, N absorpstion increased by 57,70%, P absorpstion increased by 155%, K absorpstion increased by 44.27%, whereas of Tegar genotype the N absorpstion increased by 61.50%, P absorpstion increased by 69.30%, K absorpstion increased by 60.61%. The germination rate and seedling growth rate of the two genotype are only affected by the application of P fertilizer. The index vigor of Laris and Tegar was only affected by both AMF and P fertilizer application. Keywords: AMF, fertilizer, Mycofer, seed quality